Frequency of Neurological Disorders Misdiagnosed as Conversion Disorder in our Local Population - Ayesha Siddiqa Butt, Sadia Abdul Jabbar, Waleed Akhtar, Amjad Hussaain Balouch, Hateem Bakhsh Sobhi, Hanniyah Abdul Jabbar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and Objectives: To determine the frequency of Neurological Disorders, Misdiagnosed as Conversion Disorder in our local population Study Design: Cross sectional study Place and Duration of Study: Study was conducted at Psychiatry Department, Akhtar Saeed Medical College & Hospital, Lahore Pakistan, from June, 2021 to December, 2021. Data Collection: After meeting the inclusion criteria 115 patients were enrolled. CT brain, MRI brain and EEG were carried out to assess neurological symptoms in patients admitted with a diagnosis of conversion disorder. Misdiagnosis was labeled as per operational definition. All the data analyzed on SPSS version 23. Results: In this study the mean age was (27.03±11.95) years, male to female ratio was 0.36:1. The CT and MRI diagnosed abnormal finding in 7(6.1%) patients, while EEG was abnormal in 2(1.7%) of these 7 patients, resulting in neurological disorders being diagnosed in 7(6.1%) patients. Hence, in this study misdiagnosed cases were 7(6.1%). Conclusion: This study concluded that frequency of Neurological Disorders Misdiagnosed as Conversion Disorder is 6.09% in our local population. Keywords: Conversion Disorder, Neurological disorder, EEG, MRI, CT